ANALYSIS OF NATURALIST INTELLIGENCE OF STUDENTS IN CLASS XI IPS OF SANTO LEO HIGH SCHOOL, WEST JAKARTA - Fellix Rimba; Nandi Nandi; Annisa Joviani Astari (Universitas Sebelas Maret (UNS), 2023)
This study aims to determine the level of naturalist intelligence of students in class XI of Santo Leo High School, West Jakarta. This research uses descriptive-qualitative method. The population and sample in this study used Simple Random Sampling with students in class XI IPS SMA Santo Leo West Jakarta as many as 32 people. the instrument used in this study is a questionnaire related to naturalist intelligence. The results showed that the naturalist intelligence of students in class XI IPS SMA Santo Leo West Jakarta was classified as a high category with a score of 3.89. As explained in detail the achievement of each indicator is Distinguishing members of a species gets a score of 4.10 with a high category, Recognizing the existence of species with a penchant for being in the open nature of the medium category (3.54), Mapping the relationship between several species, either formally or informally with a score of 4.00 (High category) and Researching natural symptoms with a score of 3.90 which is classified as high.